Papillion-Lefèvre Syndrome: Periodontists’ Perspective - Sunil Kumar Biraggari; K. Krishna Mohana Reddy; J. Sudhakar; Shiva Shankar Bugude; Rajesh Nichenametla; Mazher Ahmed Hakeem; Swati Reddy Tiyyagura (Case Reports in Dentistry)
Papillion-Lefèvre Syndrome is a very rare disorder of autosomal recessive inheritance distinguished by palmar plantar hyperkeratosis and early onset of periodontitis affecting the dentition. Genetic studies have identified a mutation in the major gene locus of chromosome 11q14 with loss of function. Cathepsin C gene is to be responsible for Papillion-Lefèvre Syndrome. The present case report describes a 13-year-old female, who visited the Department of Periodontology with the chief compliant of bleeding gums and loose teeth. She presented with the signs and symptoms of Papillion-Lefèvre Syndrome. The patient had premature shedding of her deciduous dentition. On clinical examination, extraorally, the patient presented with persistent thickening, flaking, and scaling of the skin of palms and soles. Her intraoral examination revealed gingival inflammation, abscess formation, and periodontal pockets. Her intraoral radiographs showed bone loss involving the central incisors and molars. The patient underwent periodontal therapy and is under maintenance.